Catalyst for catalytic oxidation of organic pollutants as well as preparation method and application of catalyst
By using ZIF-62@MIL-53 composite catalysts, using its multi-channel structure and stable glass framework to solve the problem of low existing catalyst catalytic efficiency, and achieve efficient degradation of difficult degradation organic pollutants.
Patent Information
- Application Number
- CN202411486481.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
When existing catalysts treat difficult-to-degrade organic industrial wastewater, the catalytic efficiency is low, resulting in low degradation efficiency of difficult-to-degrade organic pollutants.
ZIF-62@MIL-53 composite catalyst is used. The catalyst is composed of ZIF-62 vitrified framework and MIL-53 inserts. It is prepared through grinding and mixing, EDTA chelation and vitrification/crystal modification to form porous channels. MOF crystal-glass composites.
The catalytic efficiency and selectivity of the catalyst are improved, the structural stability and active site utilization of MIL-53 are enhanced, and the degradation efficiency of refractory organic pollutants is significantly improved.
Smart Images

Figure CN119346176A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalyst technology, and in particular to a catalyst for catalytic oxidation of organic pollutants, a preparation method and an application thereof. Background Art
[0002] The printing and dyeing and papermaking industries play an important role in the national economic construction and are also the main source of industrial wastewater pollution in my country. Their wastewater contains a large amount of difficult-to-degrade organic pollutants, which has the typical characteristics of difficult-to-degrade organic industrial wastewater. The annual wastewater discharge COD accounts for more than 10% of the total COD of industrial wastewater discharge in my country. The benzene-based difficult-to-degrade pollutants contained in the wastewater of the printing and dyeing and papermaking industries are characterized by large quantity, high toxicity and difficulty in biological removal.
[0003] Advanced oxidation technology is a technology commonly used in water treatment and air purification. Its core is to use strong oxidizing free radicals (mainly hydroxyl free radicals) to degrade organic pollutants. In the advanced oxidation process, catalysts play a vital role. At present, the mineralization treatment path using chemical advanced oxidation technology is the mainstream method for treating difficult-to-degrade organic industrial wastewater. Through the strong oxidizing effect of inorganic free radicals, large molecular difficult-to-degrade organic pollutants are decomposed into small molecular organic pollutants, and finally degraded into CO 2 and H 2 O. However, the mineralization treatment route needs to overcome the stable chemical structure of the refractory organic pollutants, and the catalytic efficiency of existing catalysts is low, resulting in low degradation efficiency of refractory organic pollutants under this route. Therefore, how to improve the catalytic efficiency of catalysts is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides a catalyst for catalytic oxidation of organic pollutants, a preparation method and an application thereof, in order to solve the following technical problem: how to improve the catalytic efficiency of the catalyst.
[0005] In a first aspect, the present application provides a catalyst for catalytically oxidizing organic pollutants, wherein the catalyst is a ZIF-62@MIL-53 composite catalyst, and the ZIF-62@MIL-53 composite catalyst comprises:
[0006] ZIF-62 vitrified framework; and
[0007] A MIL-53 insert, wherein the MIL-53 insert is embedded in the ZIF-62 vitrified framework.
[0008] Optionally, the mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (1-9): (1-9).
[0009] Optionally, the mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (2-3):1.
[0010] In a second aspect, the present application provides a method for preparing a ZIF-62@MIL-53 composite catalyst as described in any one of the first aspects, the method comprising:
[0011] Grinding and mixing ZIF-62 and MIL-53 according to a set ratio to obtain a first precursor;
[0012] Mixing the first precursor with an EDTA chelating agent to obtain a second precursor;
[0013] The second precursor is vitrified / crystallized to obtain a ZIF-62@MIL-53 composite catalyst.
[0014] Optionally, the mass ratio of the first precursor to the EDTA chelating agent is 1:(1-10).
[0015] Optionally, the mass ratio of the first precursor to the EDTA chelating agent is 1:2.
[0016] Optionally, the temperature of the glass transition / crystal modification is 350° C. to 450° C., and the time of the glass transition / crystal modification is 30 min to 60 min.
[0017] In a third aspect, the present application provides an application of a ZIF-62@MIL-53 composite catalyst as described in any one of the embodiments in the first aspect in removing refractory organic pollutants in wastewater.
[0018] Optionally, the application includes:
[0019] The ZIF-62@MIL-53 composite catalyst and an oxidant are added to wastewater containing refractory organic pollutants to carry out an advanced oxidation reaction; the refractory organic pollutants contain phenolic hydroxyl groups and / or phenoxy functional groups.
[0020] Optionally, the mass concentration of the ZIF-62@MIL-53 composite catalyst is 2 g / L to 5 g / L.
[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0022] The present application provides a catalyst for catalytic oxidation of organic pollutants, the catalyst is a ZIF-62@MIL-53 composite catalyst, the ZIF-62@MIL-53 composite catalyst includes: a ZIF-62 glass framework; and a MIL-53 insert, the MIL-53 insert is embedded in the ZIF-62 glass framework. The ZIF-62@MIL-53 composite catalyst forms a multi-porous MOF crystal-glass composite material. On the one hand, the glass framework of ZIF-62 provides a stable supporting environment for MIL-53, preventing the structural collapse and active site deactivation of MIL-53 during the catalytic reaction; on the other hand, the pore structure and active sites of MIL-53 form a close interaction with the framework of ZIF-62, promoting the catalytic reaction. The resulting synergistic catalytic effect enables the ZIF-62@MIL-53 composite catalyst to show higher activity and selectivity in the catalytic reaction. Thereby improving the catalytic efficiency of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0025] Figure 1 A schematic flow chart of a method for preparing a ZIF-62@MIL-53 composite catalyst provided in an embodiment of the present application;
[0026] Figure 2 The nitrogen adsorption-desorption curves of the specific surface areas of ZIF-62, MIL-53 and ZIF-62@MIL-53 composite catalysts provided in Example 2 of the present application;
[0027] Figure 3 The SEM image of ZIF-62 provided in Example 2 of the present application;
[0028] Figure 4 The SEM image of MIL-53 provided in Example 2 of the present application;
[0029] Figure 5 This is a SEM image of the ZIF-62@MIL-53 composite catalyst provided in Example 2 of the present application;
[0030] Figure 6XRD diagram of the ZIF-62@MIL-53 composite catalyst provided in Examples 1 to 5 of the present application;
[0031] Figure 7 This is a diagram showing the recycling effect of the ZIF-62@MIL-53 composite catalyst of Example 2 provided in Example 9 of the present application. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0033] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0034] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0036] The present application provides a catalyst for catalytically oxidizing organic pollutants, wherein the catalyst is a ZIF-62@MIL-53 composite catalyst, and the ZIF-62@MIL-53 composite catalyst comprises:
[0037] ZIF-62 vitrified framework; and
[0038] A MIL-53 insert, wherein the MIL-53 insert is embedded in the ZIF-62 vitrified framework.
[0039] It should be noted that ZIF-62, full name Zinc Imidazolate Framework-62, is also known as Zn-ZIF-62. CAS No.: 1446434-44-1. Molecular formula: C 28 H 26 N16 Zn 4 , where the ligands are mainly imidazole and its derivatives. The metal center of ZIF-62 is zinc (Zinc) ions, which are connected to organic ligands through coordination bonds to form a stable skeleton structure. The organic ligands of ZIF-62 are mainly imidazole (Imidazole) and its derivatives, which combine with zinc ions through specific chemical reactions to form MOF materials with specific structures and functions. ZIF-62 is highly crystalline and porous, and its pore size and shape can be regulated by adjusting the structure of organic ligands and synthesis conditions. ZIF-62 also has super glass-forming ability, and can form large pieces of transparent glass through processes such as melt quenching, showing unique physical and chemical properties.
[0040] MIL-53 is a porous crystalline structure formed by the interconnection of metal ions (such as chromium, aluminum or iron) and organic ligands. As a type of MOF material, MIL-53 has a highly ordered porous structure, and these pores can be used to load molecules, gases or other substances, thus giving it a variety of functions and applications. MIL-53 has a specific porous structure, and the pore size and shape can be regulated by adjusting the types and synthesis conditions of metal ions and organic ligands. Due to its porous structure, MIL-53 usually has a higher specific surface area, which gives it advantages in adsorption, catalysis and other fields. In addition, the structure and function of MIL-53 can be regulated by changing the types and synthesis conditions of metal ions and organic ligands to meet different application requirements.
[0041] The ZIF-62@MIL-53 composite catalyst in the embodiment of the present application is an innovative MOF crystal-glass composite material, which consists of two parts: ZIF-62 glass framework: ZIF (Zeolitic Imidazolate Frameworks) is a type of metal organic framework material with imidazole or its derivatives as ligands and transition metal ions as nodes. In this composite catalyst, ZIF-62 is designed as a glass framework, that is, a stable structure is formed through a vitrification process at a relatively low temperature. This glass framework not only has excellent mechanical stability, but also effectively protects the MIL-53 embedding embedded therein. MIL-53 embedding: MIL-53 is another metal organic framework material with a unique pore structure and active sites. In the ZIF-62@MIL-53 composite catalyst, MIL-53 is embedded in the glass framework of ZIF-62 as an embedding. This design allows the pore structure and active sites of MIL-53 to be maintained, thereby giving full play to its catalytic or adsorption properties.
[0042] The ZIF-62@MIL-53 composite catalyst in the embodiment of the present application forms a multi-porous MOF crystal-glass composite material (MOF-CGC). This multi-porous structure is conducive to the diffusion and contact of the reactant inside the catalyst, thereby improving the catalytic efficiency. At the same time, through the vitrification process of ZIF-62, the stable framework formed effectively protects the MIL-53 embedded object to prevent it from structural damage or active site deactivation during the reaction process. This enhanced stability enables the composite catalyst to be used in a wider range of temperature and pressure. In addition, since the MIL-53 embedded object is cleverly embedded in the vitrification framework of ZIF-62, the active sites in its pores can be more in contact with the reactant. This design improves the utilization rate of the active sites and further improves the catalytic performance.
[0043] In some embodiments, the mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (1-9): (1-9).
[0044] In the composite, the combination of ZIF-62 glass framework and MIL-53 inserts aims to optimize the performance of the composite by adjusting the mass ratio of the two. This composite combines the unique pore structure of ZIF-62 and the catalytic activity of MIL-53. When the proportion of ZIF-62 is high, the overall framework of the composite will be mainly composed of ZIF-62, and its three-dimensional network structure and porosity can provide more stable support. This helps to maintain the pore structure of the composite and prevent collapse during catalysis or adsorption. On the contrary, when the proportion of MIL-53 is high, although the number of active sites is increased, the stability of some frameworks may be sacrificed. Therefore, a balance needs to be found to ensure the stability of the framework and the effectiveness of the active sites. As a catalytically active material, the content of MIL-53 directly affects the catalytic efficiency of the composite. As the proportion of MIL-53 increases, the number of active sites also increases accordingly, which may improve the efficiency of the catalytic reaction. However, an excessively high proportion of MIL-53 may cause the active sites to be too crowded, which in turn reduces the catalytic efficiency. Therefore, it is necessary to optimize the ratio of the two according to the specific catalytic reaction and conditions.
[0045] Therefore, the embodiment of the present application rationally designs the mass ratio of the ZIF-62 glass framework to the MIL-53 insert to be (1 to 9): (1 to 9). The combination of the ZIF-62 glass framework and the MIL-53 insert can effectively adjust the framework and pore structure stability and the number of active sites of the composite material. By optimizing this ratio, precise control of the catalytic efficiency of the composite material can be achieved. Exemplarily, the mass ratio of the ZIF-62 glass framework to the MIL-53 insert can be 1:1, 1:3, 1:5, 1:7, 1:9, 9:1, 7:1, 5:1, 3:1, 2:1, etc.
[0046] In some embodiments, the mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (2-3):1.
[0047] Preferably, the mass ratio of the ZIF-62 glass framework to the MIL-53 insert is limited to (2-3):1, thereby further improving the catalytic efficiency.
[0048] Figure 1 A schematic flow chart of a method for preparing a ZIF-62@MIL-53 composite catalyst provided in an embodiment of the present application.
[0049] See also Figure 1 The present application provides a method for preparing the ZIF-62@MIL-53 composite catalyst as described in any one of the above, the method comprising:
[0050] S1, grinding and mixing ZIF-62 and MIL-53 according to a set ratio to obtain a first precursor;
[0051] The pre-synthesized ZIF-62 and MIL-53 are fully ground and mixed in a set ratio (such as 1-9:1-9) to ensure that the two are evenly dispersed. The purpose of this step is to form a preliminary physical mixture, namely the first precursor.
[0052] In some embodiments, the preparation method of ZIF-62 specifically comprises the following steps: weighing 0.5346 g Zn(NO 3 ) 2 6H 2 O, 0.21264g benzimidazole and 0.2451g imidazole were dissolved in 30ml DMF, and the resulting solution was transferred to a polytetrafluoroethylene liner, and then the reactor was placed in an oven and kept at a constant temperature of 130°C for 48h. The reactor was taken out and cooled and crystallized at room temperature. White crystals of ZIF-62 (Zn) were obtained after filtration, centrifuged and washed twice, dried, and sealed for later use.
[0053] In some embodiments, the preparation method of MIL-53 specifically comprises the following steps: adding a certain amount of FeCl 3 and H 2 BDC was placed in DMF and magnetically stirred for 1 h, then placed in a reactor and kept at 150°C for 20 h. After naturally cooling to room temperature, the precipitate was collected by high-speed centrifugation and finally dried at 60°C to obtain a yellow powdery final product.
[0054] S2, mixing the first precursor with an EDTA chelating agent to obtain a second precursor;
[0055] The first precursor is mixed with EDTA (ethylenediaminetetraacetic acid) chelating agent. EDTA, as a strong chelating agent, can form a stable complex with metal ions, which helps to adjust the distribution and stability of metal ions in subsequent steps. The mixture obtained in this step is called the second precursor.
[0056] In some embodiments, the mass ratio of the first precursor to the EDTA chelating agent is 1:(1-10).
[0057] As a strong chelating agent, EDTA can form a stable complex with metal ions. In the early stage of the preparation of the composite catalyst, EDTA can penetrate into the MOFs material (ZIF-62 and MIL-53) and combine with the metal ions as the active center to form a complex. This complex can prevent the metal ions from being oxidized during the preparation process, thereby protecting the integrity and activity of the active center. At the same time, by adjusting the mass ratio of the first precursor to the EDTA chelating agent to 1: (1-10), the degree of formation and stability of the complex can be controlled. When the EDTA content is moderate, a sufficient number of complexes can be formed to protect the metal ions. The right amount of EDTA chelating agent not only helps to protect the metal ions, but also has a positive effect on the pore structure, specific surface area and other properties of the composite material. In addition, when a certain treatment temperature (such as about 400°C) is reached, the complex between EDTA and the metal ions will decompose and volatilize. At this time, the metal ions (i.e., active sites) originally protected by the complex are fixed in the pore structure of the composite material, maintaining their activity and stability. Exemplarily, the mass ratio of the first precursor to the EDTA chelating agent can be 1:1, 1:3, 1:5, 1:7, 1:8, 1:9, 1:10, etc.
[0058] In some embodiments, the mass ratio of the first precursor to the EDTA chelating agent is 1:2.
[0059] S3. Vitrifying / crystallizing the second precursor to obtain a ZIF-62@MIL-53 composite catalyst.
[0060] During the vitrification / crystallization modification of the second precursor (i.e., the product of the mixture of ZIF-62 and MIL-53 and EDTA chelating agent), ZIF-62 undergoes a glass transition to form a stable glassy framework. During this process, the molecular structure of ZIF-62 is reorganized to form a more compact and stable network structure. While ZIF-62 is vitrified, MIL-53 can maintain its original form and embed into the glassy framework of ZIF-62 due to the stability of its crystal structure. This embedding effect is achieved through intermolecular interaction forces (such as van der Waals forces, hydrogen bonds, etc.). In addition, the EDTA chelating agent plays a key role in the vitrification / crystallization modification process. It can form a stable complex with metal ions to prevent metal ions from being oxidized or undergoing other adverse reactions at high temperatures. At the same time, the presence of EDTA also helps to regulate the pore structure and active site distribution of the material.
[0061] In some embodiments, the vitrification / crystal modification is specifically as follows: the second precursor is placed in an atmosphere furnace, heated at a set heating temperature, kept warm for a certain period of time, and then rapidly quenched.
[0062] In some embodiments, the temperature of the glass transition / crystal modification is 350° C. to 450° C., and the time of the glass transition / crystal modification is 30 min to 60 min.
[0063] The temperature of glass transition / crystal modification is limited to 350℃~450℃, and ZIF-62 can undergo glass transition and form a stable glassy structure. This glassy structure has high mechanical strength and chemical stability, which can effectively protect the embedded MIL-53 inserts and maintain the overall structure of the composite material. At the same time, it can also produce a certain crystal modification effect on MIL-53. Appropriate crystal modification may help optimize the pore structure and active site distribution of MIL-53, thereby improving its catalytic efficiency. If the temperature is lower than 350℃, ZIF-62 cannot be fully vitrified, resulting in insufficient stability of the composite material. In addition, the temperature below 350℃ may not effectively promote the crystal modification of MIL-53. If the temperature exceeds 450℃, the glass transition of MIL-53 will be triggered, thereby destroying its crystal structure and active sites. This will not only reduce the catalytic efficiency of MIL-53, but may also have an adverse effect on the performance of the entire composite material. The time of glass transition / crystal modification is limited to 30min~60min, which can ensure that the glass transition process of ZIF-62 is fully carried out. Exemplarily, the temperature of glass transition / crystal modification can be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 420°C, 440°C, 450°C, etc., and the time of glass transition / crystal modification can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0064] The product prepared by the preparation method of the ZIF-62@MIL-53 composite catalyst is the above-mentioned ZIF-62@MIL-53 composite catalyst. The chemical composition and structure of the ZIF-62@MIL-53 composite catalyst prepared by the preparation method of the ZIF-62@MIL-53 composite catalyst can refer to the above-mentioned embodiment. Since the preparation method of the ZIF-62@MIL-53 composite catalyst adopts part or all of the technical solutions of the ZIF-62@MIL-53 composite catalyst embodiment, it has at least all the beneficial effects brought by the technical solutions of the ZIF-62@MIL-53 composite catalyst embodiment, which will not be repeated here one by one.
[0065] Based on a general inventive concept, the present application provides an application of a ZIF-62@MIL-53 composite catalyst as described in any one of the above embodiments in removing refractory organic pollutants in wastewater.
[0066] In some embodiments, the application comprises:
[0067] The ZIF-62@MIL-53 composite catalyst and an oxidant are added to wastewater containing refractory organic pollutants to carry out an advanced oxidation reaction; the refractory organic pollutants contain phenolic hydroxyl groups and / or phenoxy functional groups.
[0068] In some embodiments, the mass concentration of the ZIF-62@MIL-53 composite catalyst is 2 g / L to 5 g / L.
[0069] In some embodiments, the oxidizing agent includes one or more of hydrogen peroxide, monopersulfate, and dipersulfate.
[0070] In some embodiments, the ratio of the mass concentration of the oxidant to the mass concentration of the refractory organic pollutant is 1:(0.1-100).
[0071] In some embodiments, the parameters of the advanced oxidation reaction include: reaction temperature of 20°C to 45°C, stirring speed of 300rpm to 500rpm, and reaction time of 5min to 60min.
[0072] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0073] Example 1
[0074] This embodiment provides a ZIF-62@MIL-53 composite catalyst. The preparation method of the ZIF-62@MIL-53 composite catalyst comprises the following steps:
[0075] S1, grinding and mixing ZIF-62 and MIL-53 in a mass ratio of 9:1 to obtain a first precursor;
[0076] S2, mixing the first precursor and the EDTA chelating agent in a mass ratio of 1:2 to obtain a second precursor;
[0077] S3, heating the second precursor in an atmosphere furnace at 400° C. and keeping the temperature for 30 min, and then rapidly quenching to obtain a ZIF-62@MIL-53 composite catalyst.
[0078] Based on the ZIF-62@MIL-53 composite catalyst prepared in Example 1, this example also provides an application of the ZIF-62@MIL-53 composite catalyst in removing refractory organic pollutants in wastewater, specifically comprising the following steps:
[0079] The ZIF-62@MIL-53 composite catalyst was ground into powder, and then the ZIF-62@MIL-53 composite catalyst powder was added to 500 ml of wastewater containing 5 mg / L BPA, and reacted for 30 minutes at a temperature of 25°C and a stirring speed of 500 rpm. The catalyst addition amount was 0.5 g / L, the oxidant addition amount was 100 mg / L, and the catalytic degradation effect of BPA is shown in Table 1.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-62 to MIL-53 is 7:3.
[0082] Figure 2 The nitrogen adsorption-desorption curves of the specific surface areas of ZIF-62, MIL-53 and ZIF-62@MIL-53 composite catalysts provided in Example 2 of the present application are shown in FIG. Figure 2 It can be seen that MOFs material itself is a material with a high specific surface area. The specific surface areas of synthesized ZIF-62 and MIL-53 both reach 160m 2 / g and 270m 2 / g or more. However, after ZIF-62 alone was vitrified at 400°C, the specific surface area of ZIF-62 was greatly reduced, while the specific surface area of ZIF-62@MIL-53 composite material did not change significantly compared with MIL-53, indicating that the specific surface area of the whole material showed the characteristics of the framework structure.
[0083] Figure 3The SEM image of ZIF-62 provided in Example 2 of the present application; Figure 4 The SEM image of MIL-53 provided in Example 2 of the present application; Figure 5 This is a SEM image of the ZIF-62@MIL-53 composite catalyst provided in Example 2 of the present application. Figures 3 to 5 It can be seen that Figure 4 The synthesized MIL-53 has a typical rhombohedral structure, which is consistent with previous studies. Figure 3 The surface morphology of ZIF-62 itself before vitrification is relatively rough, while the fired catalyst can be seen to have obvious smooth characteristics, indicating that ZIF-62 becomes liquid at high temperature and transforms into a precise glass phase during quenching to form a MOF crystal-glass composite material (MOF-CGC).
[0084] Figure 6 XRD diagram of the ZIF-62@MIL-53 composite catalyst provided in Examples 1 to 5 of the present application. CAT in the figure represents the ZIF-62@MIL-53 composite catalyst, ZIF-62@MIL-53 (9:1) represents the ZIF-62@MIL-53 composite catalyst obtained in Example 1 with a mass ratio of ZIF-62 to MIL-53 of 9:1, and the rest are similar. Figure 6 It can be seen that after MIL-53 and ZIF-62 are mixed in a certain mass ratio and vitrified at 400°C, the characteristic diffraction peak of ZIF-62 disappears, but the characteristic peak of MIL-53 is still partially retained, indicating that the catalyst may be a MOF crystal-glass composite material (MOF-CGC). With the increase of the amount of MIL-53, after high-temperature calcination, the characteristic diffraction peak of ZIF-62 gradually disappears, but some characteristic peaks of MIL-53 are still retained. Taking advantage of the fact that the melting point of ZIF-62 is lower than its decomposition degree, MIL-53 is protected during the vitrification process of ZIF-62, and the open pore structure of MIL-53 is maintained, so that the active sites in the pores can be more in contact with the reactants.
[0085] Example 3
[0086] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-62 to MIL-53 is 5:5.
[0087] Example 4
[0088] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-62 to MIL-53 is 3:7.
[0089] Example 5
[0090] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-62 to MIL-53 is 1:9.
[0091] Example 6
[0092] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-62 to MIL-53 is 1:0.3, and the mass ratio of the first precursor to the EDTA chelating agent is 1:1.
[0093] Example 7
[0094] The difference between this embodiment and embodiment 6 is that the mass ratio of the first precursor to the EDTA chelating agent is 1:3.
[0095] Example 8
[0096] The difference between this embodiment and embodiment 6 is that the mass ratio of the first precursor to the EDTA chelating agent is 1:5.
[0097] Example 9
[0098] In order to explore the recycling of the ZIF-62@MIL-53 composite catalyst, the ZIF-62@MIL-53 composite catalyst of Example 2 was subjected to a recycling experiment, which specifically included the following steps:
[0099] The ZIF-62@MIL-53 composite catalyst powder was added to 500 ml of wastewater containing 5 mg / L BPA, and the reaction was carried out at a temperature of 25°C and a stirring speed of 500 rpm for 60 min. 10 ml of water sample was taken for measurement, wherein the catalyst addition amount was 0.5 g / L and the oxidant addition amount was 100 mg / L. After the reaction was completed, 10 ml of 0.5 mg / ml BPA solution was added, stirred evenly, and then the oxidant was added. The reaction was carried out at a stirring speed of 500 rpm for 60 min, wherein the oxidant addition amount was 100 mg / L. This was repeated 8 times.
[0100] Figure 7 This is a diagram showing the recycling effect of the ZIF-62@MIL-53 composite catalyst of Example 2 provided in Example 9 of the present application. Figure 7 It can be seen that the ZIF-62@MIL-53 composite catalyst has good recycling ability. After ten cycles, it still has a degradation performance of nearly 90%, which fully demonstrates the stability of the catalyst.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 1 is that ZIF-62 is used alone as a catalyst for the catalytic degradation of BPA.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that MIL-53 is used alone as the catalyst for the catalytic degradation of BPA.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 6 is that the mass ratio of the first precursor to the EDTA chelating agent is 4:1.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 1 is that the mass ratio of ZIF-62 to MIL-53 is 1:0.3, and the heating temperature in the atmosphere furnace is 200°C.
[0109] Comparative Example 5
[0110] The difference between this comparative example and comparative example 4 is that the heating temperature in the atmosphere furnace is 300°C.
[0111] Comparative Example 6
[0112] The difference between this comparative example and comparative example 4 is that the heating temperature in the atmosphere furnace is 500°C.
[0113] Comparative Example 7
[0114] The difference between this comparative example and comparative example 4 is that the heating temperature in the atmosphere furnace is 700°C.
[0115] Table 1 Catalytic degradation effect of BPA in Examples 1 to 8 and Comparative Examples 1 to 7
[0116] Group BPA removal rate COD removal rate Example 1 82.6% 65.3% Example 2 93.9% 76.5% Example 3 90.1% 70.4% Example 4 89.3% 71.3% Example 5 81.2% 69.7% Example 6 82.6% 68.9% Example 7 86.8% 70.4% Example 8 73.5% 61.2% Comparative Example 1 19.4% 11.3% Comparative Example 2 56.1% 35.8% Comparative Example 3 61.4% 45.3% Comparative Example 4 27.6% 10.1% Comparative Example 5 36.7% 15.3% Comparative Example 6 52.7% 23.1% Comparative Example 7 42.4% 31.2%
[0117] As shown in Table 1, in Examples 1 to 8, the use of ZIF-62@MIL-53 composite catalyst can achieve effective degradation of refractory organic matter at low oxidant dosage. At the same time, different synthesis methods such as temperature, precursor ratio, and chelating agent usage have a great influence on the performance of ZIF-62@MIL-53 composite catalyst. In Comparative Examples 1 to 2, ZIF-62 and MIL-53 are used alone as catalysts, and the catalytic degradation performance is much lower than that of ZIF-62@MIL-53 composite catalyst, indicating that in ZIF-62@MIL-53 composite catalyst, ZIF-62 and MIL-53 play a synergistic catalytic role. In Comparative Examples 4 to 7, both high and low temperatures will cause the composite structure to fail to form. At 200 and 300 ° C, ZIF-62 not only cannot be vitrified, but also collapses with MIL-53, and the effect is poor. After the heating temperature reaches 500 and 700 ° C, MIL-53 also undergoes vitrification and structural collapse, and the effect is poor.
[0118] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:
[0119] In the examples of the present application, by screening different vitrification / crystallization modification conditions, a stable ZIF-62@MIL-53 composite catalyst is formed to remove difficult-to-degrade organic pollutants in wastewater from the printing and dyeing and papermaking industries. Compared with the Fenton treatment project and ordinary ZIF-62 and MIL-53 MOFs catalytic materials, it has a better removal rate and a lower oxidant dosage.
[0120] In the examples of the present application, the prepared ZIF-62@MIL-53 composite catalyst has a BPA removal rate of ≥70% in sewage and a COD removal rate of ≥60% in wastewater.
[0121] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A catalyst for catalytic oxidation of organic pollutants, characterized in that: The catalyst is a ZIF-62@MIL-53 composite catalyst, and the ZIF-62@MIL-53 composite catalyst comprises: ZIF-62 vitrified framework; and A MIL-53 insert, wherein the MIL-53 insert is embedded in the ZIF-62 vitrified framework.
2. The catalyst according to claim 1, characterized in that The mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (1-9): (1-9).
3. The catalyst according to claim 2, characterized in that The mass ratio of the ZIF-62 vitrified framework to the MIL-53 embedding is (2-3):
1.
4. A method for preparing the ZIF-62@MIL-53 composite catalyst according to any one of claims 1 to 3, characterized in that: The method comprises: Grinding and mixing ZIF-62 and MIL-53 according to a set ratio to obtain a first precursor; Mixing the first precursor with an EDTA chelating agent to obtain a second precursor; The second precursor is vitrified / crystallized to obtain a ZIF-62@MIL-53 composite catalyst.
5. The method according to claim 4, characterized in that The mass ratio of the first precursor to the EDTA chelating agent is 1:(1-10).
6. The method according to claim 4, characterized in that The mass ratio of the first precursor to the EDTA chelating agent is 1:
2.
7. The method according to claim 4, characterized in that The temperature of the glass transition / crystal modification is 350° C. to 450° C., and the time of the glass transition / crystal modification is 30 min to 60 min.
8. Use of the ZIF-62@MIL-53 composite catalyst as claimed in any one of claims 1 to 3 in removing refractory organic pollutants in wastewater.
9. The use according to claim 8, characterized in that: The applications include: The ZIF-62@MIL-53 composite catalyst and an oxidant are added to wastewater containing refractory organic pollutants to carry out an advanced oxidation reaction; the refractory organic pollutants contain phenolic hydroxyl groups and / or phenoxy functional groups.
10. The use according to claim 8, characterized in that: The mass concentration of the ZIF-62@MIL-53 composite catalyst is 2 g / L to 5 g / L.